Against Human Trade In Steven Spielberg's Amistad Movie (1997): A Marxist Criticism - Luqmana, Hanung; , Dr. M. Thoyibi, M.S; , Titis Setyabudi, S.S. M. Hum (2014)
The major problem of this study is how social relation and stratification is reflected in Steven Spielberg‟s Amistad based on Marxist perspective. This study aims to describe the internal structure of the film script and to describe the social relation and stratification in Steven Spielberg‟s Amistad Film Script based on Marxist Perspective. The benefits of this study are to enrich the application of Marxist Perspective in literary study and to fulfill the requirement for getting Bachelor Degree in English Department. The type of this research is descriptive qualitative research. The primary data is taken from the film script, itself, while the secondary data is taken from information needed. The method of data collection is library research. The technique of data collection is descriptive. The outcome of the study shows that there is a close relationship between the film scripts and the social reality of America in late twentieth century, racism and classes that raise the gap between them. It is why Steven Spielberg criticizes that condition. This film script represents one of Spielberg‟s concerns in social humanity.